Analisis Advokasi Wahana Lingkungan Hidup Indonesia Jambi dalam Penanganan Pencemaran Sungai Batanghari Akibat Tambang Ilegal - Marcelia Amanda Slaliahi; Michael Lega; Suci Rahmadani (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
This study examines the environmental advocacy strategies carried out by WALHI Jambi in addressing the pollution of the Batanghari River caused by illegal gold mining activities. This issue reflects ongoing environmental degradation and weak policy enforcement in managing natural resources. The study aims to analyze advocacy practices in terms of raising public awareness, community organizing, and influencing policy. A qualitative approach with a case study method was employed, with data collected through in-depth interviews, observation, and document analysis. The findings show that WALHI Jambi has undertaken various advocacy efforts, including media campaigns, public actions, community assistance, and engagement in policy forums. However, these efforts remain not fully optimal. Public awareness initiatives are still limited to information dissemination, community organizing has not yet developed into a strong collective movement, and policy influence is constrained by the absence of systematic instruments such as formal documentation, litigation, and structured coalitions. This study contributes to the understanding of environmental advocacy practices and highlights the need for strengthening advocacy strategies to achieve more effective policy influence and sustainable environmental governance.